Production of flat and hollow fiber membranes for Biodialysis application - Lee, Kuan Yet (Faculty of Chemical and Natural Resource Engineering, 2007)
Since the results in the previous study indicated that the ratio of acetic acid/PEG is a significant factor, different types of PEG are used in this stage of the study. Different molecular weight of PEG was added into the dope formulations at different ratios. Several tests were carried out as to validate the dialysis membrane produced. All the tests were conducted according to the parameter and methodology described in Chapter 3, section 3.2 and individual additional testing condition would be discussed as follows.